Effects of blastocyst elongation and implantation chamber formation on the alignment of the embryonic axis and uterine axis in mice - Sakurai, Jun; Oka, Sanae; Higuchi, Yoko; Ohsawa, Sonoko; Fujimori, Toshihiko (Frontiers in Cell and Developmental Biology, 2024)
Embryo implantation involves a series of events that bring the embryo and maternal tissues into contact to support post-implantation development in mammals. During implantation, alignment of the embryonic–abembryonic (E–Ab) axis of the blastocyst with the mesometrial–antimesometrial (M–AM) axis of the uterus precedes post-implantation embryonic development and placentation. In the present study, we observed the morphological changes in blastocysts and the endometrial luminal epithelium (LE) that occur during the alignment of the embryonic and the uterine axes. We found that at the time that the blastocysts attached to the LE at the mural trophectoderm, the embryonic axis was not aligned with the uterine axis. Alignment of the embryonic E–Ab axis with the uterine M–AM axis occurred after E4.0, and the embryo was significantly elongated during the process. The depth of the implantation chamber (IC) correlated with the degree of alignment, suggesting that elongated embryos are oriented along the M–AM axis during IC formation. Transplantation of the Concanavalin A (Con A)–coated beads induced IC formation, and the alignment of two Con A–coated beads present in the same IC in the M–AM direction suggested that elongated materials can align along the M–AM axis. These data suggest that an elongated shape of the embryo and IC formation coordinate the alignment of the embryonic and uterine axes.